A revision of the New Zealand Tyrini (Coleoptera, Staphylinidae, Pselaphinae), with the description of two new genera and five new species. Issue 1 (2nd January 2021) - Hlaváč, Peter
ABSTRACT: Four Tyrini genera occurring in New Zealand are revised: Agatyrus Broun T. 1917. Descriptions of new genera and species of Coleoptera (Part V). New Zealand Institute, Bulletin No. 1, pp. 347–474. John Mackay, Wellington, Gerallus Sharp, 1874, Plesiotyrus Broun, 1914 and Zeatyrus Sharp, 1881. Two new genera, Hamotyrus gen. nov. and Plesiotyrinus gen. nov., and five new species, Agatyrus erectotibialis sp. nov., Hamotyrus nunni sp. nov., Plesiotyrinus kuscheli sp. nov., Plesiotyrinus occidentalis sp. nov., and Plesiotyrus tibialis sp. nov., are described. A lectotype is designated for Agatyrus fulvihirtus Broun T. 1917. Descriptions of new genera and species of Coleoptera (Part V). New Zealand Institute, Bulletin No. 1, pp. 347–474. John Mackay, Wellington. Zeatyrus is transferred to the subtribe Somatipionina. All genera have diagnoses provided, together with drawings of the aedeagi of all treated species. A key to the genera of New Zealand Tyrini, as well as keys for each genus treated here, are provided.